Analytical Study of Pippalyadigana Vati - An Ayurvedic Formulation (International Journal of Ayurveda and Pharma Research, 2024)
In Ayurveda, the raw drugs are classified under various groups known as Gana, which contain substances with comparable qualities that can treat a particular ailment. Ganas are very crucial to making the treatment field simpler and more efficient. Acharya Sushrut made a truly remarkable contribution by classifying the drugs into 37 distinct categories for various ailments. Pippalyadi gana is one of the Ganas described by Acharya Sushruta and is specially mentioned for the management of Pratishyaya. Pratishyaya is one important disease of Urdhwajatrugata Roga. In Ayurveda, Kalka, Kawath, Churna and Vati are the most frequently used form of medication. Vati preparation is considered a secondary Kashaya Kalpana and offers an easy way to administer oral medication. In the present study, 14 drugs from Pippalyadi Gana were selected for Vati preparation and certain of them were used in Kwath form for Bhavna, while the drugs containing volatile oils were utilized in powder form. Vati Kalpana has been prepared according to general method of preparation Vati mentioned in API. Prepared Vati were tested by many parameters including physical and chemical ones, such as weight variation and disintegration time, and chromatographic tests, such as TLC fingerprinting, were used to standardize it. After the testing, all parameters were found to be within API standard limits. This kind of result indicates a good therapeutic property of Vati Kalpana which can be used as oral medication for Pratishyaya.